25-Hydroxyvitamin D serum levels and melanoma risk: a case–control study and evidence synthesis of clinical epidemiological studies. Issue 3 (May 2019) - Cattaruzza, Maria Sofia; Pisani, Daniela; Fidanza, Laura; Gandini, Sara; Marmo, Giovanna; Narcisi, Alessandra; Bartolazzi, Armando; Carlesimo, Marta
Abstract : There is accumulating evidence that the vitamin D pathway may play a role in melanoma. The aim of this study was to investigate the association between 25-hydroxyvitamin D [25(OH)D] serum levels and the risk of cutaneous melanoma. A case–control study with 137 incident cases of melanoma (serum samples collected at the time of diagnosis) and 99 healthy controls (serum samples collected between October and April) was carried out and evaluated in the framework of an evidence synthesis of clinical epidemiological studies on the topic to facilitate comparisons and summarize the scientific evidence produced so far. There was a statistically significant difference in the median levels of serum vitamin D between melanoma patients and healthy controls (18.0 vs. 27.8 ng/ml, P <0.001). Among melanoma patients, 66.2%, compared with 15.2% of healthy controls, had vitamin D deficiency (⩽20 ng/ml), whereas vitamin D sufficiency (≥30 ng/ml) was observed in only 7.4% of melanoma patients and in 37.4% of the healthy controls ( P <0.001). A multivariate model including age, sex, and BMI showed a statistically significant inverse association between melanoma and vitamin D sufficiency versus deficiency (odds ratio=0.04; 95% confidence interval: 0.02–0.10, P <0.001). Also, vitamin D insufficiency versus deficiency was significantly inversely associated with melanoma (odds ratio=0.13; 95% confidence interval: 0.06–0.27, P <0.001). These results suggest that both deficient and insufficient serum levels of vitamin D are associated with melanoma and that a trend seems to be present with a reduced risk of melanoma when vitamin D approaches normal values.